PENURUNAN BOD PADA BIOGAS KOTORAN SAPI CAMPURAN LIMBAH CAIR INDUSTRI PENYAMAKAN KULIT DENGAN VARIASI KECEPATAN DAN LAMA PENGADUKAN - Indrawati, Rosiana (Journal of Research and Technology, 2017)
The scarcity of energy sources, especially fuel oil (BBM) has become a world problem. The abundant cattle dung in the community has not been optimally utilized. In addition, the Tannery Industry (IPK) has not been optimally utilized. The aim of this research is to know the effect of speed and duration of stirring to biogas volume and final BOD concentration on cow manure biogas mixturetannery industry wastewater (IPK). The experiment used biodigester reactor as much as 5 pieces, 1 as the controller without stirring and 4 others as the test digester with stirring. IPK 0 as a control digester without stirring. Variation of stirring speed 5 and 10 rpm and stirring time 10 and 15 minutes. The volume of biogas is measured for 20 days. BOD levels are measured on the last day of the fermentation process. The experiment showed that the highest biogas volume was found on PK10L10 test digester that was mixture of cow manureandtannery industry wastewater (IPK) with variation of 10 rpm and duration of stirring 10 minutes ie 0.904 m3, and the lowest biogas volume was 0,158 m3in IPK0 digester. The highest decrease in BOD content was 20% in PK10L15 digester and the lowest decrease IPK0 digester was 4%. The stirring process has a significant effect on biogas production and decrease of BOD concentration in the digester.